Analysis of the Impact of Material Flow Cost Accounting (MFCA) on the Circular Economy: The Mediating Role of Sustainable Financial Strategies (Empirical Study on Personal Care Companies in Indonesia, Malaysia, and Thailand 2020–2024) - Irsyad Maulana; Sugiyanto; Firman Tatariyanto (LP2M IAIN Palopo, 2026)
This study analyzes the effect of Material Flow Cost Accounting (MFCA) on the circular economy with sustainable finance strategy as a mediating variable in personal care companies listed on the Indonesia, Malaysia, and Thailand stock exchanges for the 2020-2024 period, amidst the challenges of plastic waste in the ASEAN cosmetics sector. The objective is to test the causal relationship and mediation role using a quantitative panel data regression approach. The population includes non-cyclical consumer companies, a purposive sample of 70 observations from annual reports. Instruments include the CE Index (10 indicators), MFCA ratio, and SDGs Index (17 indicators) via content analysis; the analysis includes the Chow-Hausman test, regression, and Sobel test. The results show that MFCA has a significant negative effect on the circular economy (β=-0.409, p=0.042), sustainable finance strategy has a positive effect (β=1.128, p<0.001), but does not mediate (H2 is not significant). In conclusion, companies need to strategically integrate MFCA into green investments for an effective circular transition.